Delayed HBV reactivation in rituximab-containing chemotherapy: How long should we continue anti-virus prophylaxis or monitoring HBV-DNA?. (November 2016) - Nakaya, Aya; Fujita, Shinya; Satake, Atsushi; Nakanishi, Takahisa; Azuma, Yoshiko; Tsubokura, Yukie; Hotta, Masaaki; Yoshimura, Hideaki; Ishii, Kazuyoshi; Ito, Tomoki; Nomura, Shosaku
Highlights: Reactivation of HBV infection is potentially fatal complication treated with rituximab. There is no consensus over what time period antiviral prophylaxis and/or monitoring should occur. We have reported 5 cases of delayed HBV reactivation. The use of 12-month follow-up periods, which many guidelines recommend, may not be sufficient. Physicians should keep monitoring even if this requires longer than guideline recommended. Abstract: Reactivation of hepatitis B virus (HBV) infection is a well-recognized and potentially fatal complication in patients treated with chemotherapy for lymphoid malignancies. Although several guidelines recommend antiviral prophylaxis and/or monitoring for HBV-DNA, there is no consensus over what time period these should occur. Clinically, we have encountered delayed reactivation of HBV infections and have reported 12 cases of reactivation in patients. Among them, five patients developed HBV reactivation more than a year after they completed their chemotherapy. This means there can be a delayed HBV reactivation and prolonged monitoring of more than a year after cessation of chemotherapy may be needed. Hence, the current recommendation of stopping antiviral prophylaxis 6–12 months after the cessation of chemotherapy may not fully protect all patients from HBV reactivation. The optimal duration of follow-up needs to be determined, and until better guidelines are set, there is no choice but to keep monitoring patients for reactivation for as long as practicable.